2023
DOI: 10.1039/d2tb01875f
|View full text |Cite
|
Sign up to set email alerts
|

Response of mesenchymal stem cells to surface topography of scaffolds and the underlying mechanisms

Abstract: The critical role and mechanism of the topography of materials to regulate the function and fate of mesenchymal stem cells are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 179 publications
0
5
0
Order By: Relevance
“…Recently, studies on the biocompatibility, resistance to bacterial infection or physical stress [36], material composition for biological functions [37], surface roughness [38], modulus of elasticity [39], and surface topology/morphology [40] have been conducted to improve the function of implantable materials. In addition to these mechanical and physical functions, drug-holding and delivery capabilities are considered important parameters for predicting biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on the biocompatibility, resistance to bacterial infection or physical stress [36], material composition for biological functions [37], surface roughness [38], modulus of elasticity [39], and surface topology/morphology [40] have been conducted to improve the function of implantable materials. In addition to these mechanical and physical functions, drug-holding and delivery capabilities are considered important parameters for predicting biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological and other geometric characteristics of PET substrates can exert influence on the adhesion, proliferation, and differentiation of Mesenchymal Stem Cells (MSCs) on their surfaces ( Xiao et al, 2023 ). For instance, surface morphology, including features such as surface roughness and texture, can impact MSC adhesion, subsequently affecting their proliferation and differentiation ( Tang et al, 2010 ; Song et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiphoton-based 3D protein micropatterning allows human skin fibroblasts to be cultured on protein micropillar arrays with independently controllable stiffness, and it was found that cells preferentially sense the stiffness of the microenvironment rather than the elastic modulus . In addition, the surface topography of materials plays an important role in tissue engineering, for example, the morphology and differentiation of MSCs can be precisely regulated by specific scales of topography . Substrate materials of biological scaffolds can affect cell regeneration and organoid formation in tissue engineering from the surface to the inside.…”
Section: Elements Affecting Hair Cycle and Strategies To Promote Hair...mentioning
confidence: 99%